Labor Union Objectives and Collective Bargaining - Blair, Douglas H.; Crawford, David L. (Quarterly Journal of Economics, 1984)
We consider a model oflabor union behavior in which workers make decisions about wages and employment by simple majority rule. We show that under general conditions such a union has a well-behaved objective function, different from those previously postulated in the literature. We then show that the union's majority preferences generally lack a von Neumann-Morgenstern utility representation and thus cannot be inserted into traditional bargaining models. We then develop and characterize the solutions to a new bargaining model that is consistent with the structure of union preferences. Several comparative-statics results are presented.